Pengaruh Kebiasaan Belajar Siswa terhadap Hasil Belajar Siswa Kelas IV SDN 200307 Padang Sidempuan - Salsabilah Alyshah; Dody Feliks P. Ambarita; Elvi Mailani; Robenhart Tamba; Masta Marselina Sembiring (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to determine the influence of students' learning habits on learning outcomes in Mathematics subjects in grade IV students of SD Negeri 200307 Padang Sidempuan. The background of this research is the importance of the role of structured and consistent learning habits in supporting the achievement of optimal learning outcomes, especially in logical and analytical subjects such as Mathematics. This study uses a quantitative approach with a descriptive survey method to obtain an objective picture of the relationship between variables. The population in this study is all grade IV students, and the sampling technique was carried out by purposive sampling, with a sample of 26 students selected based on certain criteria. Data collection was carried out through an instrument in the form of a Likert scale questionnaire as many as 60 previously validated statements, in order to measure the level of students' learning habits. Meanwhile, student learning outcome data is obtained from their academic scores in Mathematics subjects. Data analysis was carried out using a parametric statistical test in the form of a t-test to test the proposed hypothesis. The test results showed that the tcount value of 1.909 was greater than the ttable of 1.695, which means that there was a significant influence between students' learning habits on Mathematics learning outcomes. Thus, it can be concluded that good study habits make a real contribution to improving student learning outcomes. These findings are an important basis for teachers and schools to continue to encourage and foster positive learning habits among students. The implications of this study also recommend the need to strengthen independent learning strategies and effective study time management as part of the learning program in elementary schools.